Resection vs. Sorafenib for Hepatocellular Carcinoma With Macroscopic Vascular Invasion: A Real World, Propensity Score Matched Analytic Study - Mei, Jie; Li, Shao-Hua; Wang, Qiao-Xuan; Lu, Liang-He; Ling, Yi-Hong; Zou, Jing-Wen; Lin, Wen-Ping; Wen, Yu-Hua; Wei, Wei; Guo, Rong-Ping (Frontiers in Oncology, 2020)
Background. Macroscopic vascular invasion (MVI) commonly occurs in patients with advanced hepatocellular carcinoma (HCC) for which resection and sorafenib are the common therapies prescribed. Here, we aimed to compare the survival outcomes of these two therapies in HCC patients with MVI. Methods. In total, 488 patients diagnosed with HCC and MVI without extrahepatic metastasis, treated with resection (resection-based group, n=380) and sorafenib (sorafenib-based group, n=108) were included in this study. A one-to-one propensity score-matching analysis (PSM) was performed to minimize the effect of potential confounders. Results. The median OS in the resection- and sorafenib-based group was 20.9 months (95% CI: 16.8–25.2) and 11.6 months (95% CI: 8.4–14.9) (p <0.001), respectively. The median PFS was 4.7 months (95% CI: 3.7–5.7) in the resection-based group and 4.4 months (95% CI: 3.6–5.2) in the sorafenib-based group (p<0.001). After PSM, 72 patients from each group were matched. The median OS was 27.2 months (95% CI: 16.4–38.0) in the resection-based group and 13.0 months (95% CI: 9.6–16.3) in the sorafenib-based group (p <0.001). The median PFS was 5.3 months (95% CI: 3.2–7.4) in the resection-based group and 4.8 months (95% CI: 3.6–6.0) in the sorafenib-based group (p=0.061). Conclusion. Findings from this study showed that, compared with sorafenib-based treatment, surgical resection might be associated with better survival benefits to HCC patients with MVI.